Students’ Ability in Writing Descriptive Text - Sri Rahmadhani Siregar; Nursahara Dongoran (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
The aim of this research was to find out the students’ ability in writing descriptive text at grade VII SMP N 11 Padangsidimpuan. This research was descriptive quantitative method that was conducted at SMP N 11 Padangsidimpuan. The population of this research was the grade VII students of SMPN 11 Padangsidimpuan consist of 70 students from 3 classes as the sample of the research. The data were collected from students’ writing test. In writing test, there are generic structure and language features. The indicators divided into some sub indicators, generic structure is divided into identification and description. While language features is divided into some sub indicators, there are: the usage of simple present tense, specific participant, using attributive and identifying process, using adjective, and using classifier in nominal group. The mean score of the students’ writing descriptive text mastery was 78.5. The result of this research showed the students writing descriptive text mastery in good category.